Inclusive leadership - Davis, Shirley (Tantor Media, Inc., 2024)
Inclusive Leadership For Dummies helps leaders successfully navigate the nuances of a diverse workforce and create a culture where ALL talent can thrive. Toss out the one-size-fits-all leadership approaches, because the workforce is not a monolith-it's a rich and beautiful tapestry made up of people from all backgrounds, cultures, skills, and experiences. This book enables you to develop the knowledge and competencies needed to lead diverse teams successfully. It also provides tips, tools, and techniques, for how to proactively respond to external pressures and disruptions like the changing workforce, marketplace, and the political and economic climate for how to foster and ensuring that all employees are included, valued, they feel safe, and they can do their best work.
Online resource; title from title details screen (O'Reilly, viewed July 2, 2024)
Keywords: Leadership -- Philosophy; Leadership; Philosophie; Audiobooks; Livres audio